The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1093/mnras/staa2480
|View full text |Cite
|
Sign up to set email alerts
|

The SEDIGISM survey: molecular clouds in the inner Galaxy

Abstract: We use the 13CO (2-1) emission from the SEDIGISM (Structure, Excitation, and Dynamics of the Inner Galactic InterStellar Medium) high-resolution spectral-line survey of the inner Galaxy, to extract the molecular cloud population with a large dynamic range in spatial scales, using the Spectral Clustering for Interstellar Molecular Emission Segmentation (scimes) algorithm. This work compiles a cloud catalogue with a total of 10663 molecular clouds, 10300 of which we were able to assign distances and compute phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 145 publications
(252 reference statements)
4
22
0
Order By: Relevance
“…In the Milky Way, GMCs have long been known as good tracers of spiral arms (e.g., Myers et al, 1986;Grabelsky et al, 1988;Hou and Han, 2014). From the wealthy dataset of Galactic CO surveys (see Heyer and Dame, 2015, for a review), a large number of isolated molecular clouds have been identified by different methods (e.g., García et al, 2014;Rice et al, 2016;Miville-Deschênes et al, 2017;Yan et al, 2020;Duarte-Cabral et al, 2021). For the majority of them, only kinematic distances are known, which depend on the adopted Galaxy rotation curve, the solution of the kinematic distance ambiguity, and deviation from the hypothetic circular rotation.…”
Section: Giant Molecular Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Milky Way, GMCs have long been known as good tracers of spiral arms (e.g., Myers et al, 1986;Grabelsky et al, 1988;Hou and Han, 2014). From the wealthy dataset of Galactic CO surveys (see Heyer and Dame, 2015, for a review), a large number of isolated molecular clouds have been identified by different methods (e.g., García et al, 2014;Rice et al, 2016;Miville-Deschênes et al, 2017;Yan et al, 2020;Duarte-Cabral et al, 2021). For the majority of them, only kinematic distances are known, which depend on the adopted Galaxy rotation curve, the solution of the kinematic distance ambiguity, and deviation from the hypothetic circular rotation.…”
Section: Giant Molecular Cloudsmentioning
confidence: 99%
“…For the majority of them, only kinematic distances are known, which depend on the adopted Galaxy rotation curve, the solution of the kinematic distance ambiguity, and deviation from the hypothetic circular rotation. For instance, Duarte-Cabral et al (2021) compiled a large catalogue of 10,663 molecular clouds in the inner Galaxy. They estimated the kinematic distances for 10,300 clouds after solving the distance ambiguities through different methods.…”
Section: Giant Molecular Cloudsmentioning
confidence: 99%
“…The validity of these scaling relations has been challenged both in the local environment and in extragalactic targets with different environmental conditions. Most observations do find a correlation between the size and the linewidth, but there seems to be no agreement for the power-law exponent and all observations find large uncertainties in the slope (Duarte-Cabral et al 2020;Imara et al 2020). Moreover, the third Larson relation is likely to be an artefact produced by the limited dynamical range of early observations of column density, and the sample of observed clouds being located in similar environmental conditions.…”
mentioning
confidence: 93%
“…The trends are observed, but the scatter is large, and different surveys reach different conclusions for the exponents. Within the disc, no strong variations of GMC properties in relation to the position in the disc are observed (Duarte-Cabral et al 2020).…”
mentioning
confidence: 95%
See 1 more Smart Citation